RESEARCH ON OBTAINING A SOFT DRINK WITH NUTRACEUTICAL POTENTIAL, BASED ON COCA COLA AND ORANGE JUICE - MARIA LIDIA D. IANCU (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
Iconic Coca-Cola and premium orange juice are the most consumed soft drinks and juices in the world. In the present study the obtention five samples of soft drink by mixing the two beverages in different proportion, 1:0.125, 1:0.25, 1:0.5, 1:1 and 1:2 was described. The physicochemical and sensory characteristics were described. The determined quality indicators were the following: the relative density, the soluble dry matter, the total acidity, the turbidity, the kinematic viscosity, the soluble dry matter/titratable acidity, the carbon dioxide, the vitamin C, the sensory analysis. Compared to the Coca-Cola and premium orange juice control samples, the consumer’s favorite was the sample with Coca Cola: premium orange juice - ratio 1:2. The values of the quality indicators of this innovative combination are in the range of known values for the non-alcoholic beverages, but the CO2 content is 1.52 g/100 cm3 and that of the ascorbic acid is 467 ppm. The 467 ppm increase in the vitamin C content as compared to Coca-Cola, which contains 0 ppm, can place this sample in the category of the nutraceutical beverages naturally enriched with vitamin C.